Othering Ourselves: Reflections on Method, Identity, and Ethics (Reflections on Unexpected Encounters in Participatory Research) - Virginia Navarro; Jane Zeni (Disability Studies Quarterly, 2004)
Broun's and Heshusius's paper, Unexpected encounters in participatory research: Meeting the abled? /disabled? self when researching the lives of disabled women, unmasks the intertwining of personal and professional realities while engaging in research. Reflecting on and extending these issues, we critically unpack three central concepts: 1) The evolving choice of appropriate method in interpretive inquiry involves thinking through relational issues and our own theoretical understandings; 2) Attending closely to multi-voiced meanings in dialogue with others expands understandings of our own potential selves, and 3) Research activity inevitably involves ethical conundrums around both the relational and interpretive processes. In this commentary, the authors attempt to broaden the disability focus of Broun's experience by revisiting tensions around method, voice, and identity that apply broadly to everyone who conscientiously engages in ethical situated inquiry. The "I" as well as the "Thou" may be metamorphosed through qualitative inquiry.